Methods and Experimental Techniques in Computer Engineering - Amigoni, Francesco; Schiaffonati, Viola; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Computing and science reveal a synergic relationship. On the one hand, it is widely evident that computing plays an important role in the scientific endeavor. On the other hand, the role of scientific method in computing is getting increasingly important, especially in providing ways to experimentally evaluate the properties of complex computing systems. This book critically presents these issues from a unitary conceptual and methodological perspective by addressing specific case studies at the intersection between computing and science. The book originates from, and collects the experience of, a course for PhD students in Information Engineering held at the Politecnico di Milano. Following the structure of the course, the book features contributions from some researchers who are working at the intersection between computing and science.
Computational Models for Environmental Systems -- How Far Chemistry and Toxicology Are Computational Sciences? -- Good Experimental Methodologies for Autonomous Robotics: From Theory to Practice -- RAWSEEDS: Building a Benchmarking Toolkit for Autonomous Robotics -- Biorobotics: A Methodological Primer.
Keywords: Engineering; Artificial intelligence; Computer science; Engineering; Computational Intelligence; Computer Applications; Artificial Intelligence (incl. Robotics).